Bulk synthesis of octa- and nonamethylfluorene (Flu '' H and Flu*H) and the characterization of the organometallic derivatives Flu*SnMe3, [(FeCp)(2)Flu*H][PF6](2), and [(FeCp)(2)Flu '' H][PF6](2) - Moss, J; Thomas, J; Ashley, A; Cowley, A; O'Hare, D (2006)
The large-scale synthesis of two highly methylated fluorene ligands is reported, and the synthesis and characterization of three organometallic derivatives are reported. Starting with 1,2,3,4-tetramethylbenzene, 1,2,3,4,5,6,7,8-octa- and 1,2,3,4,5,6,7,8,9-nonamethylfluorene (Flu"H and Flu*H) have been synthesized in overall yields of above 50%. Both fluorenes may be deprotonated at the 9 position to yield useful organometallic synthons; the Sn derivative, Flu*SnMe3, is synthesized using this reagent, and its molecular structure has been elucidated. The Fe bimetallics [(FeCp)2Flu*H][PF6]2 and [(FeCp)2Flu″H][PF6]2 have been isolated, and their electrochemical properties ascertained. Electrochemical measurements on these complexes show the methylated fluorene ligand acts as a strong electron donor and acts to increase the electronic communication between the metal centers, in comparison with the nonmethylated analogues. The solid-state structure of [(FeCp)2Flu*H][PF6]2 has been determined and, unlike the Sn complex, does not show a significantly twisted fluorenyl core. © 2006 American Chemical Society.